Fool's gold: major sport events and foreign direct investment - Jakobsen, J.; Solberg, H. A.; Halvorsen, T.; Jakobsen, T. G. (International Journal of Sport Policy and Politics, 2013)
Whether or not a city or a country should bid to host the Olympics or one of the big international football tournaments is often the source of heated debates. One question that is always raised is whether hosting such an event yields positive economic benefits. Using data from the period 1970-2009 we investigate whether there is a link between hosting a major sport event and the amount of foreign direct investment (FDI) a country receives. We employ time-series cross-section data for countries that have hosted either the Summer Olympics, the Winter Olympics, the FIFA World Cup or the UEFA European Championship in that period. While our overall results, on balance, offer support to the `pessimistic` side of the debate about the economic effects of hosting mega events, our findings also indicate that some FDI benefits might still accrue to the host. Results are not unambiguous, however. More detailed analysis suggests that staging the Olympics has virtually no effect on FDI inflows, whereas hosting a major, nationwide football tournament might have a small positive impact on foreign investment, particularly in the years leading up to the event. These latter results seem to be driven by smaller nations.